(untitled) (Global Journal of Science Frontier Research, 2012)
The mosquito repellent activity of phytochemical extracts from Peels of five citrus fruit species, Citrus sinensis, Citrus limonum,Citrus aurantifolia, Citrus reticulata and Citrus vitis, was investigated. The volatile phytochemical extracts were obtained from processed air-dried and powdered citrus fruit peels by Soxchlet extraction using Diethyl Ether as solvent. Five different concentrations, 5%, 10%, 15%, 20% and 25% (volume by volume) were prepared from each extract stock. Topical application of the extract concentrations on human volunteers revealed that 20% and 25% repelled mosquitoes 2 hours and 5 hours, respectively. Short-lived and mild skin itching and sneezing reactions were observed as side effects. This study has shown that phytochemical extracts from species of citrus fruit have good promise for topical repellence against mosquitoes generally.